Curcumin Inhibits Cell Proliferation, Stimulates Apoptosis and Down-Regulates Aldehyde Dehydrogenase Expresion in Gastric cancer Cell line MKN45 - Hung, Nguyen Phu; Thanh Huong, Le Thi; Thanh, Nguyen Trung (VNU Journal of Science: Natural Sciences and Technology, 2020)
According to estimates by the World Health Organization (WHO), in 2018 there were over one million new stomach cancer patients. Vietnam ranks the tenth among the countries with the highest rates of stomach cancer in the world, with the rate of 15.9 cases per 100,000 populations. Research on compounds or drugs that can inhibit cancer cell growth but are less toxic to the body is necessary. In this study, using MTT assays, we have shown that curcumin has ability to inhibit proliferation of stomach cancer cells MKN45. Flow cytometry analysis showed that curcumin increased the percentage of apoptosis cells by 27 - 56% at concentrations of 10 µM - 20 µM and resulted in a typical nuclear morphology of apoptosis. Further, this study showed that curcumin significantly reduced the expression of aldehyde dehydrogenase protein in MKN45 gastric cancer cells. This finding shows that curcumin is a potential therapeutic candidate for gastric cancer cell treatment.